Molecular imaging of cancer by glucosamine chemical exchange saturation transfer MRI: A preclinical study. (26th October 2020) - Rivlin, Michal; Navon, Gil
Abstract : Glucosamine (GlcN) was recently proposed as an agent with an excellent safety profile to detect cancer with the chemical exchange saturation transfer (CEST) MRI technique. Translation of the GlcN CEST method to the clinical application requires evaluation of its sensitivity to the different frequency regions of irradiation. Hence, imaging of the GlcN signal was established for the full Z spectra recorded following GlcN administration to mice bearing implanted 4T1 breast tumors. Significant CEST effects were observed at around 1.5, 3.6 and −3.4 ppm, corresponding to the hydroxyl, amine/amide exchangeable protons and for the Nuclear Overhauser Enhancement (NOE), respectively. The sources of the observed CEST effects were investigated by identifying the GlcN metabolic products as observed by 13 C NMR spectroscopy studies of extracts from the same tumor model following treatment with [UL‐ 13 C] ‐GlcN·HCl. The CEST contribution can be attributed to several phosphorylated products of GlcN, including uridine diphosphate‐N‐acetylglucosamine (UDP‐GlcNAc), which is a substrate for the O‐linked and N‐linked glycosylated proteins that may be associated with the increase of the NOE signal. The observation of a significant amount of lactate among the metabolic products hints at acidification as one of the sources of the enhanced CEST effect of GlcN. The proposed method may offer a new approach for clinical molecular imaging that enables the detection of metabolically active tumors and may play a role in other diseases. Abstract : Glucosamine (GlcN) was recently proposed as an agent with an excellent safety profile to detect cancer by using the chemical exchange saturation transfer (CEST) MRI technique. In this study, tumor metabolic profile was examined by using in vivo Z spectra for implanted breast tumors in mice before and at two time periods after GlcN uptake alongside investigation of its main metabolites in tumors that contribute to the total CEST contrast.